(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2013)
Local wisdom of Uma Lengge traditional houses were really knowledge developed by local people, obtained through a process of trial & error, as the process to be able adapt the physical environment. Located in Mbawa village, west nusa tenggara province, the building has proven to be able of adapting to the humid tropical climate with an average daily temperature 25oC. However, that potential was not consistent in the field facts that shows the Uma Lengge traditional houses waning existence. This is a separate issue, assessments, tend to raise the extent of the physical characteristics building and has not been touched in terms of scientific study of science building. This paper will examine the Uma Lengge thermal characteristics as scientific input on potential local wisdom. Measurements focused on climate parameters (temperature, humidity, and velocity) for 24 hours in the wet and dry season. The results show that Uma Lengge able to warm the 0.1 ° C in the wet season and able to refrigerate 0.8 °C in the dry season compared with outdoor temperature. This is a hidden potential that ought to be kept preserved.